The Effect Of Upright Position On Pain Stage I Active Phase Of Labor For Primiparous Mothers At The Jumpandang Baru Health Center, Makassar - Nur Ismi Wahyuni; Nur Anita (International Journal of Medicine and Health, 2023)
The first stage process is accompanied by pain which is a physiological process, a subjective experience of physical sensations associated with uterine contractions, dilatation and effacement of the cervix. Primiparous mothers often worry because they don't understand how to deal with childbirth. Primiparas tend to experience more anxiety, causing tension and fear so that they cannot endure the pain. The aim of this study was to find out the effect of the upright position on pain during the first stage of the active phase of labor for primiparous mothers at the Jumpandang Baru Health Center, Makassar. This type of research is quantitative experimental with a Post Test Only One Group Design approach. The population in this study were all mothers giving birth at the Jumpandang Baru Makassar Community Health Center from April to June 2023. The sample in this study was part of the population of mothers giving birth at the Jumpandang Baru Makassar Community Health Center from April to June 2023, totaling 15 people. with Purposive Sampling sampling technique.